γ-tocotrienol inhibits angiogenesis-dependent growth of human hepatocellular carcinoma through abrogation of AKT/mTOR pathway in an orthotopic mouse model - Siveen, K.; Ahn, K.; Ong, T.; Shanmugam, M.; Li, F.; Yap, W.; Kumar, Alan Prem; Fong, C.; Tergaonkar, V.; Hui, K.; Sethi, G. (Impact Journals LLC, 2014)
Angiogenesis is one of the key hallmarks of cancer. In this study, we investigated whether γ-tocotrienol can abrogate angiogenesis-mediated tumor growth in hepatocellular carcinoma (HCC) and if so, through what molecular mechanisms. We observed that γ-tocotrienol inhibited vascular endothelial growth factor (VEGF)-induced migration, invasion, tube formation and viability of HUVECs in vitro. Moreover, γ-tocotrienol reduced the number of capillary sprouts from matrigel embedded rat thoracic aortic ring in a dose-dependent manner. Also, in chick chorioallantoic membrane assay, γ-tocotrienol significantly reduced the blood vessels formation. We further noticed that γ-tocotrienol blocked angiogenesis in an in vivo matrigel plug assay. Furthermore, γ-tocotrienol inhibited VEGF-induced autophosphorylation of VEGFR2 in HUVECs and also suppressed the constitutive activation of AKT/mammalian target of rapamycin (mTOR) signal transduction cascades in HUVECs as well as in HCC cells. Interestingly, γ-tocotrienol was also found to significantly reduce the tumor growth in an orthotopic HCC mouse model and inhibit tumor-induced angiogenesis in HCC patient xenografts through the suppression of various biomarkers of proliferation and angiogenesis. Taken together, our findings strongly suggest that γ-tocotrienol might be a promising anti-angiogenic drug with significant antitumor activity in HCC.